RETRACTED: Berberine Suppresses Stemness and Tumorigenicity of Colorectal Cancer Stem-Like Cells by Inhibiting m6A Methylation - Zhao, Ziyi; Zeng, Jinhao; Guo, Qiang; Pu, Kunming; Yang, Yi; Chen, Nianzhi; Zhang, Gang; Zhao, Maoyuan; Zheng, Qiao; Tang, Jianyuan; Hu, Qiongying (Frontiers in Oncology, 2021)
Background: Cancer stem cells (CSCs) are able to survive after cancer therapies, resulting in tumor progression and recurrence, as is seen in colorectal cancer. Therapies targeting CSCs are regarded as novel and promising strategies for efficiently eradicating tumors. Berberine, an isoquinoline alkaloid extracted from the Chinese herbal medicine Coptis chinensis, was found to have antitumor activities against colorectal cancer, without knowing whether it exerts inhibitory effects on colorectal CSCs and the potential mechanisms. Methods: In this study, we examined the inhibitory roles of berberine on CSCs derived from HCT116 and HT29 by cultured in serum-free medium. We also examined the effects of berberine on m6A methylation via regulating fat mass and obesity-associated protein (FTO), by downregulating β-catenin。 Results: we examined the effects of berberine on the tumorigenicity, growth and stemness of colorectal cancer stem-like cells. The regulatory effect of berberine on N6-methyladenosine (m6A), an abundant mRNA modification, was also examined. Berberine treatment decreased cell proliferation by decreasing cyclin D1 and increasing p27 and p21 and subsequently induced cell cycle arrest at the G1/G0 phase. Berberine treatment also decreased colony formation and induced apoptosis. Berberine treatment transcriptionally increased FTO and thus decreased m6A methylation, which was reversed by both FTO knockdown and the addition of the FTO inhibitor FB23-2. Berberine-induced FTO-related decreases in stemness in HCT116 and HT29 CSCs. Berberine treatment also increased chemosensitivity in CSCs and promoted chemotherapy agent-induced apoptosis. Moreover, we also found that berberine treatment increased FTO by decreasing β-catenin, which is a negative regulator of FTO. Conclusions: Our observation that berberine effectively decreased m6A methylation by decreasing β-catenin and subsequently increasing FTO suggests a role of berberine in modulating stemness and malignant behaviors in colorectal CSCs.